2001
DOI: 10.1603/0022-0493-94.2.344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Synergistic Interactions Between the Colorado Potato Beetle (Coleoptera: Chrysomelidae) Pathogen <B> <I>Beauveria bassiana</I> </B> and the Insecticides, Imidacloprid, and Cyromazine

Abstract: Laboratory studies investigated the interaction between the fungal entomopathogen Beauveria bassiana (Balsamo) Vuillemin and sublethal doses of the insecticides imidacloprid and cyromazine when applied to larvae of the Colorado potato beetle, Leptinotarsa decemlineata (Say). When second instars were fed potato leaf discs treated with sublethal doses of imidacloprid and a range of doses of B. bassiana, a synergistic action was demonstrated. Similar results were observed when larvae were sprayed directly with B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 20 publications
2
61
2
2
Order By: Relevance
“…Studies on insect hosts other than mosquitoes have indicated that fungal infection can act synergistically with insecticides, increasing the impact of otherwise sublethal insecticide doses (24)(25)(26). Mixtures of M. anisopliae and deltamethrin were shown to enhance virulence of both components when tested against ticks, indicating synergistic effects that would enhance the effectiveness of low fungi and insecticide concentrations (27).…”
mentioning
confidence: 99%
“…Studies on insect hosts other than mosquitoes have indicated that fungal infection can act synergistically with insecticides, increasing the impact of otherwise sublethal insecticide doses (24)(25)(26). Mixtures of M. anisopliae and deltamethrin were shown to enhance virulence of both components when tested against ticks, indicating synergistic effects that would enhance the effectiveness of low fungi and insecticide concentrations (27).…”
mentioning
confidence: 99%
“…In this case no effects on the rate at which conidia were removed from the cuticle were observed but feeding was inhibited when larvae were fed imidacloprid. Decreased resistance to disease is well established to increase susceptibility to pesticides (Furlong and Groden, 2001). A similar non-synergistic effect of co-exposure to imidacloprid and B. bassiana is reported in whitefly that was suggested to be due to B bassiana reducing feeding and thus intake of imidacloprid (James and Elzen, 2001).…”
Section: Interactions Of Fungal Disease and Pesticides In Other Insectsmentioning
confidence: 76%
“…Several studies have focused on the potential use of entomopathogenic fungi primarily, Beauveria bassiana (Balsamo) Vuillemin and M. anisopliae, in combination with sublethal doses of organic insecticides against various insect pests (Anderson et al, 1989;Moorhouse et al, 1992;Li and Holdom, 1994;McCoy, 1997, 1998;Furlong and Groden, 2001). Most recently, the compatibility (increased mortality and lower LT 50 ) of M. anisopliae was demonstrated with imidacloprid (Kaakeh et al, 1997), chlorpyrifos, prometamphos, and cyfluthrin (Pachamutu et al, 1999;Pachamutu and Kamble, 2000) against the German cockroach.…”
Section: Discussionmentioning
confidence: 99%